Social complexity negatively influences lung function in cystic fibrosis after transfer to adult care. Issue 1 (17th September 2019) - Crowley, Erin M.; Bosslet, Gabriel T.; Khan, Babar; Ciccarelli, Mary; Brown, Cynthia D.
Abstract: Background: Several nongenetic factors, such as socioeconomic status, environmental exposures, and adherence have been described to have an impact on outcomes in cystic fibrosis (CF). Objective: To determine the effect of social complexity on the % predicted forced expiratory volume (ppFEV1 ) before and after transfer to adult care among adolescents with CF. Methods: Retrospective, single center, cohort study included all patients with CF who were transitioned into adult care between 2005 and 2015 at Indiana University. Social complexity (Bob's level of social support, [BLSS]) was collected at transfer. Linear mixed regression models assessed the relationship between ppFEV1 decline over time and BLSS with other covariates. Results: The median age of the patients (N = 133) at the time of transfer was 20 years (interquartile range: 19‐23). Overall, there was a decline in lung function over time in our population (ppFEV1 at 24 months pretransfer 77 ± 20%, ppFEV1 at 24 months, posttransfer 66 ± 24%; P < .001). The relationship between BLSS and ppFEV1 became more negative over time, even after adjusting for other covariates. Conclusion: Social complexity is strongly associated with lung function decline after transfer to adult care.